New records of two species of oligochaetes (Naididae): Pristina longiseta and P. macrochaeta from Iraq, with notes on their morphology and reproduction - Al-Abbad , M.Y.M.; Al-Mayah, S.H. (Mesopotamian Journal of Marine Sciences, 2022)
Individuals of the two species of oligochaetes: Pristina longiseta and P. macrochaeta were identified from samples of bryophyta from shallow water areas at Al-Assafia creek which is connected to Shatt Al-Arab River. This is the first report of the two species in Iraq. The characteristic features of the two species were studied, the first important of these is the presence of dorsal setae, from the second segment in P. longiseta and from the fourth segment in P. macrochaeta. The setae of the third segment in P. longiseta are longer than the others and called giant setae. There is a conspicuous Prostomium which extends to form proboscis. Reproduction is by transverse fission which is called Paratomy.